Formulation, Quality Control and Stability Study of Pediatric Oral Dextrose Gel - Edouard Lamy; Caroline Orneto; Oumil Her Abdou Ali; Lyna Kireche; Fanny Mathias; Cyrielle Bouguergour; Florence Peyron; Nicolas Primas; Christophe Sauzet; Philippe Piccerelle; Anne-Marie Maillotte; Veronique Brevaut-Malaty; et al. (Pharmaceuticals)
Background/Objective: Little information is available on the stability and quality controls of compounded 40% dextrose gel required to ensure its safe use in the treatment and prevention of neonatal hypoglycemia. Whether its efficacy relies on buccal absorption also remains uncertain. This study investigates the stability, microbiological safety, rheological properties and dextrose diffusion of a compounded 40% oral dextrose gel, ensuring it can be widely compounded and stored for clinical use. Methods: A 40% dextrose gel compounded with anhydrous dextrose, carboxymethylcellulose, citric acid, sorbic acid and sterile water was subjected to quality control measures including a dextrose content assay, degradation product analysis, microbiological testing and preservative efficacy. Stability studies were conducted at refrigerated (4–8 °C) and ambient temperatures for 7 days and 3 months, respectively. Rheological properties were assessed, and dextrose permeation was measured through an artificial membrane model that mimics a biological membrane. Results: The compounded gel demonstrated stability for up to 7 days at ambient temperature and 90 days when refrigerated. The dextrose content remained within the acceptable range (90–110%) and microbiological tests confirmed compliance with safety standards. The gel exhibited the consistent rheological properties and shear-thinning behavior appropriate for oral mucosal administration. In vitro permeation studies showed no evidence of dextrose diffusion with a long lag time followed by a low steady-state permeation flux. Conclusions: This study validates the compounding process of a stable 40% oral dextrose gel formulation for neonatal hypoglycemia management, which meets quality control criteria and can be safely administered in clinical practice, offering a cost-effective and safe alternative for neonatal care.